Tindak Tutur Ilokusi Pengajar pada Proses Pembelajaran Bahasa Mandarin - Monika Herliana; M. Suryadi (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
Speech acts are divided into three types, namely locus speech acts, illocutionary speech acts, and perlocution speech acts. Illocutionary speech acts consist of assertive, declarative, commissive, expressive, and directive. Illocutionary can be defined as speech acts that often occur in daily interactions, one of these interactions covers the interaction between teachers and learners in educational activities in the classroom. In this activity, the teacher gives command to the students to follow the instructions. This study aims to determine the illocutionary speech acts contained in the interaction between teacher and students in using Mandarin in the classroom of D3 program of Mandarin Language, General Soedirman University, Purwokerto. This research belongs to a descriptive qualitative research. The data of this research are served in the form of speech between teacher and students during the learning of Mandarin Intermediate Conversation courses of D3 Mandarin Language Study Program UNSOED Purwokerto. The data analysis used theory of illocutionary speech acts by Austin and Searle. The data are presented in an informal form in which the data presentation and writing rules used words not numbers. The results showed that the interaction between teachers and learners in the D3 Mandarin Study Program of UNSOED Purwokerto cover assertive, declarative, commissive, expressive, and directive speech acts.